Spatiotemporal Reconstruction of Water Deities Beliefs in the Pearl River Delta Applying Historical GIS - Yuqing Liu; Yuanlin Wang (Religions, 2022)
The Pearl River Delta (PRD) is one of the most typical regions in China, where people commonly believe in Nanhaishen 南海神 (the South Sea God), Tianfei 天妃 (the Heavenly Concubine), Beidi 北帝 (the Northern Emperor) and other Water Deities. This paper investigates 40 local chronicles from 9 counties in the region. It has digitized, quantified, and analyzed the temple records of the Water Deities and used the Geographic Information System (GIS) to reconstruct the spatiotemporal evolution of the local beliefs. The results show the consistency and difference in the spatiotemporal evolution of the local beliefs of Water Deities. The consistency reflects that their original centers were all around the city of Canton and its west, namely Foshan 佛山 and Jiujiang 九江, which were in the jurisdiction of Nanhai County 南海縣, showing a similar tendency to move from the center to the periphery. The difference in the evolution is that they had apiece characteristics in distribution patterns and transmission paths. The blossoming, propagation, and consolidation of the beliefs were influenced by multi-factors such as defending against flood disasters, transportation and commercial development, the integration of national sacrifices and folk beliefs, and the connection of the beliefs with regional security. Overall, Water Deities’ status in people’s minds continued to deepen, and their supernatural powers were perceived as increasingly outstanding. It reflects people of the traditional regional society and their spiritual orientation to the material world, which was affected by institutional and non-institutional factors.